Histórias de vida e narrativas de quatro professoras normalistas - Bairros, Catia Pascotini (2018)
The present work is part of the Pedagogical Management and Educational Contexts research line of the Post-Graduate Program in Public Policies and Educational Management, Professional Master's, Federal University of Santa Maria (UFSM). The question that triggers the research is: Can life trajectories and experiences of the collaborators lead us to understand the social changes in teacher education? From this question arise others that contribute in this investigative process: What are the constructions of teaching? What do they comprise by vocational training? What is the teaching job for them? This research aims to understand the choices of professional formation and to discuss the teacher formation through the life trajectories narrated by four Normalist Professors of the State Institute of Education Olavo Bilac. The approach will be qualitative, making use of life stories in the perspective of narrative research. The collaborators were students who attended the Normal Course and who already had a degree. The work will address the trajectory of professional training of these women, teacher training and also aspects of the experience from the life narratives told by the women interviewed.